2013
DOI: 10.1063/1.4776656
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-passivated dielectric/InGaAs interfaces with sub-nm equivalent oxide thickness and low interface trap densities

Abstract: We report on the electrical characteristics of HfO 2 and HfO 2 /Al 2 O 3 gate dielectrics deposited on n-In 0.53 Ga 0.47 As by atomic layer deposition, after in-situ hydrogen or nitrogen plasma surface cleaning procedures, respectively. It is shown that alternating cycles of nitrogen plasma and trimethylaluminum prior to growth allow for highly scaled dielectrics with equivalent oxide thicknesses down to 0.6 nm and interface trap densities that are below 2.5 Â 10 12 cm À2 eV À1 near midgap. It is shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 26 publications
(36 reference statements)
2
61
0
Order By: Relevance
“…• C. For the pretreatments, each TMA cycle consisted of a 40 ms pulse at a pressure of 200 mTorr with Ar carrier gas flow of 100 sccm followed by a 5 s Ar purge, and finally a H 2 gas stabilization step for 10 s. 34,33 Each atomic hydrogen pulse was generated using an Oxford FlexAl plasma source with an ICP forward power of 100 W and consisted of exposure to the plasma for 2 s at a H 2 pressure of 20 mTorr.…”
Section: B Cleaning Studymentioning
confidence: 99%
“…• C. For the pretreatments, each TMA cycle consisted of a 40 ms pulse at a pressure of 200 mTorr with Ar carrier gas flow of 100 sccm followed by a 5 s Ar purge, and finally a H 2 gas stabilization step for 10 s. 34,33 Each atomic hydrogen pulse was generated using an Oxford FlexAl plasma source with an ICP forward power of 100 W and consisted of exposure to the plasma for 2 s at a H 2 pressure of 20 mTorr.…”
Section: B Cleaning Studymentioning
confidence: 99%
“…2 In surface channel metal oxide semiconductor (MOS) FET devices, As decapping, wet chemical processing using, for example, HF, HCl, NH 4 OH, [3][4][5] atomic hydrogen treatments, 6,7 as well as sulphur 8,9 and nitrogen passivations 10,11 have all been employed in order to remove native oxides and diminish the interaction between any deposited oxide and the semiconductor. However, while these processes have all shown improvements in device performance, the D it levels are still too high to make the incorporation of a III-V channel a viable alternative to Si in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, the surface nitridation technique has been studied as one of the promising methods for obtaining excellent Ga-based III-V surfaces. [18][19][20] It is found that the amount of the Ga-N bonds strongly correlates with D it of the oxide/nitridized-InGaAs interfaces. 18 Since nitridation and oxidation occured simultaneously in ref.…”
Section: Introductionmentioning
confidence: 99%